2019
DOI: 10.1186/s13063-019-3504-3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of xenogenic scaffolding in the context of a randomized double-blind placebo-controlled study for repairing full-thickness rotator cuff tears

Abstract: Purpose The purpose of the study was to compare the safety and efficacy of autologous mesenchymal stem cells (MSCs) embedded in a xenogenic scaffold for repairing the supraspinatus tendon. Methods This was a randomized, double-blind and placebo-controlled trial evaluating patients with full-thickness rotator cuff tears (Eudra-CT, 2007–007630-19). Effectiveness was evaluated using the Constant score and a visual analogue pain scale (VAS). Constant score has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 39 publications
(39 reference statements)
1
55
0
1
Order By: Relevance
“…After duplicates were removed, the titles and abstracts of 897 articles were initially screened and 25 selected for full-text review. The full-text articles were read and 4 were considered relevant by qualitative analysis [8,10,11,19]. The studies selected for final inclusion or exclusion are shown in Figure 1, and the characteristics of the included studies are summarized in Table 1.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After duplicates were removed, the titles and abstracts of 897 articles were initially screened and 25 selected for full-text review. The full-text articles were read and 4 were considered relevant by qualitative analysis [8,10,11,19]. The studies selected for final inclusion or exclusion are shown in Figure 1, and the characteristics of the included studies are summarized in Table 1.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…In terms of quantitative analysis, these four studies (published from 2015 to 2019) fulfilled our inclusion criteria. Three papers [8,10,19] were open-label prospective studies, while one [11] was a double-blind randomized controlled trial. The studies identified for meta-analysis included 52 participants.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations